A novel nonsingular terminal sliding mode control combined with global sliding surface for uncertain nonlinear second-order systems. (April 2020) - Liu, Weiqi; Feng, Zhengping; Bi, Anyuan
This paper proposes a novel nonsingular terminal sliding mode control combined with global sliding surface for a class of uncertain nonlinear second-order systems. The suggested control approach is developed based on the Lyapunov theory. The sliding mode reaching the sliding surface in finite time can be guaranteed. Furthermore, chattering phenomenon caused by the switching control action can be eliminated theoretically, and desirable control performance is realized. The simulation and tank test results for heave control of a remotely operated vehicle are presented to verify the effectiveness of the proposed method.